FENOMENA INTERTEKSTUALITAS DAN KLAIM ORISINALITAS - Hasbullah, Hasbullah (Universitas Hasanuddin, 2014)
Originality to a certain extent is an out of reach condition in the textual phenomenon of today. Every text is actuallya revoicing act of long in advance ideas and messages of preceding texts. Those facts have been currently analyzedand thoroghly studied by a new approach called intertextuality.This perspective claims that every text is actually an intertext, which underlines that in every text, we can encountermany voices and ideas that have long been pronounced and possessedBy the old authors. The problem lies in the fact that the ancient sources of the current text are already untraceableand nearly unidentified. The role the current writers play in producing their text is to promote new intentions to thealready made products.This approach puts a clear line of relativity in originality that every writer claims. But it gives, on the other around, anew horizon to see a kind of interrelationship among texts that will pave the way to a new method in reading themillions texts that surround us nowadays.Key words; intertext, originality, relativity, interrealtionship.